Efisiensi Teknis Usahatani Mina Padi dan Padi Konvensional di Desa Panembangan, Kabupaten Banyumas, Provinsi Jawa Tengah - Rachmanto, Ardhian; Lestari, Sri; Mulyani, Altri (Universitas Galuh, 2026)
Mina paddy is an agricultural system that has been increasingly promoted to enhance the productivity and efficiency of rice farming. This study aims to: (1) analyze distribution technical efficiency values of mina paddy and conventional paddy farming; (2) analyze the factors influencing production inefficiency in mina paddy and conventional paddy farming; and (3) analyze the level of technical efficiency in mina paddy and conventional paddy farming. Research was conducted in Panembangan Village, Cilongok Sub-district, Banyumas Regency. This study employed a quantitative descriptive approach using stochastic frontier analysis (SFA) as the analytical tool. Results indicate that land size, number of family laborers, amount of seed used (equivalent to rice seed) and quantity of herbicide applied show a significant and positive effect on rice production, additionally the amount of urea fertilizer applied has a significant and negative effect on rice production. Factors influencing the level of technical inefficiency in both mina paddy and conventional paddy farming include the farmer’s age, farming experience, and the mina paddy technology dummy variable. Overall technical efficiency values demonstrate a significant difference between the efficiency levels of mina paddy and conventional paddy farming. This indicates that the cultivation approach adopted in each farming system contributes to differences in technical performance in utilizing production inputs.